The Influence of Organizational Culture, Leadership, And Digital Skills On Employee Performance In The Polyester Division of PT. Indo-Rama Synthetics Tbk Purwakarta - Risa Alfira; Deden Sutisna (International Journal of Science and Environment (IJSE), 2025)
Organizational culture, leadership, and the use of digital technology are key factors that influence the success of organizational change. When managed properly, these aspects can have a positive impact on improving both organizational and individual performance. This study aims to determine the influence of organizational culture, leadership, and digital skills on employee performance in the Polyester Division of PT. Indo-Rama Synthetics Tbk, Purwakarta. The research method used is a descriptive quantitative approach. The population in this study consisted of all employees, totaling 1,580 individuals, with a sample of 319 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that, partially, the variables of organizational culture and leadership have a positive but not significant effect on employee performance. Meanwhile, digital skills have a negative and significant effect. Simultaneously, all three variables have a significant effect on employee performance. Digital skills contribute the most to employee performance, followed by organizational culture and leadership. This study recommends the need for targeted and adaptive improvement of employees' digital capabilities, as well as strengthening organizational culture and leadership styles that support productivity in order to enhance employee performance optimally.